ANALISIS PRILAKU AGRESIVITAS SISWA KELAS V SD NEGERI 001 SIMPANG KANAN YANG SUKA NONTON FILM LAGA TAHUN AJARAN 2013/2014 - Riadi, Selamat Riadi Selamat; Umari, Tri Umari Tri; Saam, Zulfan Saam Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study, entitled "Analysis of Behavior Aggressiveness Elementary School Grade V 001 Simpang Kanan The Love Watch Movies LagaTahun Doctrine 2014/2015". Based on observations conducted by researchers frequent commotion in class at the time of learning for students taunted each other among themselves. And most students who taunted each other are students who like to watch action movies.The aim of this study were: 1). To determine the general picture aggressiveness Elementary School fifth grade students 001 Simpang Kanan who like to watch action movies. 2). To describe the emotional verbal aggressiveness Elementary School fifth grade students 001 Simpang Kanan who like to watch action movies. 3). To describe the physical aggressiveness social Elementary School fifth grade students 001 Simpang Kanan who like to watch action movies. 4). To describe the physical aggressiveness asocial Elementary School fifth grade students 001 Simpang Kanan who like to watch action movies. 5). To find a picture of the destructive aggressiveness of public school students of class V 001 Simpang Kanan who like to watch action movies.The method used in this research is descriptive method. The population in this study were students of class V Elementary School 001 Simpang Kanan. Sample using sampling techniques that all members of the population is sampled.The results of the study are as follows: 1) In general picture of aggressiveness Elementary School fifth grade students 001 Simpang Kanan is low. 2) Judging from Emotional Verbal Aggressiveness level of aggressiveness Elementary School fifth grade students 001 Simpang Kanan who love to watch action movies were moderate. Form of emotional verbal aggressiveness among others: Anger, hate, fight, insulting and ridiculous. 3) In terms of social physical aggressiveness aggressiveness level Elementary School fifth grade students 001 Simpang Kanan is low. Social forms of physical aggression among others: fight, attack, and be harsh. 4) In terms of physical aggressiveness aggressiveness level asocial Elementary School fifth grade students 001 Simpang Kanan who like action films is low. Asocial form of physical aggression among others: demand the money, lying, and stealing. 5) In terms of destructive aggressiveness aggressiveness level Elementary School fifth grade students classified rendah.bentuk 001 Simpang Kanan destructive aggressiveness among others: kill animals, torture and self-destructive. Keywords: Teacher Knowledge, GuidanceandCounseling